Translation Students' Conception of Literary Translation Through Metaphors - Didem Tuna Küçük; Mesut Kuleli (İstanbul Üniversitesi Çeviribilim Dergisi)
The aim of this study is to analyse the metaphors about literary translation constructed by tertiary level translation students and draw implications for courses in a literary translation module. To this end, a semi-structured form including three items on literary translation was administered to final year translation students at two universities in Türkiye. As a result of the content analysis, codes were constructed for metaphors based on their foci. With the metaphors grouped under a certain code based on their relevance content-wise, the potential rationale behind each metaphor is discussed in relation to literary translation as a generic term, text analysis as part of literary translation, and translation strategies in literary translation - the three items in the semi-structured form. The data analysis yielded seven codes for literary translation as a generic term, five codes and one uncategorised response for text analysis as part of literary translation, and seven codes for translation strategies in literary translation. The study concludes that translation students reflected their perceived strengths and weaknesses in literary translation with the metaphors they constructed, which could prove significant for the teaching staff in re-evaluating and redesigning their courses in the literary translation module.